Design and implementation of a competency-based curriculum for medical education - Graciela Risco de Domínguez (Revista Peruana de Medicina Experimental y Salud Pública, 2014)
Competency-based education is a form of designing, developing, delivering and documenting instruction based on a set of objectives and results that have been recommended for medical education. This article describes the steps in the process of designing and implementing a competency-based curriculum at a new medical school in a Peruvian university. We present the process followed including context analysis, mission design, the professional profile, the content and organization of the curriculum as well as the evaluation and resources for the training. Finally, issues and challenges faced, as well as lessons learned are summarized.